2010
DOI: 10.1111/j.1740-0929.2010.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial cDNA sequence of a relaxin‐like factor (RLF) receptor, LGR8 and possible existence of the RLF ligand‐receptor system in goat testes

Abstract: Relaxin-like factor (RLF), also known as insulin-like factor 3 (INSL3), is produced by testicular Leydig cells, but its specific receptor LGR8 (leucine-rich repeat family of G-protein-coupled receptor 8) has not been identified in goats. This study aimed to identify complementary DNA (cDNA) sequences of goat LGR8, and characterize the expression of both RLF and LGR8 in goat testes by RT-PCR and immunohistochemistry. Testes were collected from immature (3-month-old) and mature (24-month-old) Saanen goats, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This finding is in good agreement with that of human RLF/INSL3, as shown by Ferlin and Foresta [31], who revealed that RLF/INSL3 is an endocrine factor. In contrast, receptor RXFP2 mRNA and/or protein have been shown to be expressed in Leydig cells and seminiferous tubule epithelial cells in adult testes of some species, including humans [5,17,32,33]. There is also evidence that RLF/INSL3 suppresses germ cell apoptosis in the rat testis [5], whereas the treatment of mouse Leydig TM3 cells with RLF/INSL3 in vitro induces cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in good agreement with that of human RLF/INSL3, as shown by Ferlin and Foresta [31], who revealed that RLF/INSL3 is an endocrine factor. In contrast, receptor RXFP2 mRNA and/or protein have been shown to be expressed in Leydig cells and seminiferous tubule epithelial cells in adult testes of some species, including humans [5,17,32,33]. There is also evidence that RLF/INSL3 suppresses germ cell apoptosis in the rat testis [5], whereas the treatment of mouse Leydig TM3 cells with RLF/INSL3 in vitro induces cell proliferation [33].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the INSL3 antibody (RLF‐A‐Ab808) was generated in our laboratory in New Zealand White rabbits against a synthetic peptide of 15 amino acid residues of the A‐domain, which shared 100% amino acid homology among porcine, bovine, ovine and caprine INSL3 complementary DNAs (cDNAs). The specificity of this antibody has been described elsewhere (Siqin et al 2010a,b, 2013; Minagawa et al ; Pitia et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed using the Vectastain Universal avidin‐biotin complex (ABC) Elite kit (Vector Laboratories, Burlingame, CA, USA) with the biotin blocking kit (Biotin Blocking System; DakoCytomation, Carpinteria, CA, USA) as previously described (Siqin et al 2010a,b, 2013; Pitia et al ). Briefly, deparaffinized 4‐μm testicular sections were incubated with anti‐INSL3 immunoglobulin G (IgG) (0.5 μg/mL), anti‐RXFP2 IgG (5 μg/mL) or antisera preabsorbed with synthetic human INSL3 (hINSL3) (25 μg/mL) (6292 Da; Phoenix Pharmaceuticals, Burlingame, CA, USA) for anti‐INSL3 (Siqin et al ) or recombinant RXFP2 endodomain peptide (400 μg/mL) for anti‐RXFP2 (Pitia et al ; Sagata et al .…”
Section: Methodsmentioning
confidence: 99%
“…The INSL3 secreted into the circulation is likely to function as an endocrine factor (Ferlin and Foresta , 2005 ), although its extra-testicular targets are undetermined. In contrast, receptor RXFP2 mRNA and/or protein have recently been shown to be expressed in Leydig cells and seminiferous germ cells in adult testes of some species (Kawamura et al , 2004 ;Anand -Ivell et al, 2006 ;Feng et al , 2007 ;Filonzi et al , 2007 ;Koeva et al , 2008 ), including goats (Siqin et al , 2010b ). Taken together with previous findings, single-chain INSL3 secreted into body fluids may function as an autocrine and/or paracrine factor in Leydig cells and seminiferous germ cells in goat testes.…”
Section: Discussionmentioning
confidence: 69%